PENGARUH PERCEIVED SECURITY DAN INFORMATION QUALITY TERHADAP ONLINE PURCHASE INTENTION MELALUI TRUST (Study Kasus Pada Konsumen Sorabel di Yogyakarta) - IBN Udayana; Putri Dwi Cahyani; Desti Nur Chotimah (Program Studi Manajemen, 2018)
The purpose of this study is to test and find out and determine the effect of perceived security and information quality on online purchase intention through trust in a reliable online store. The effect of perceived security on trust in Sorabel, the effect of information quality on trust in sorabel, the effect of perceived security on online purchase intention, the effect of information quality on online purchase intention and the influence of trust on online purchase intention. This research is quantitative. The population is Sorabel consumers in Yogyakartas. Samples were taken using a probality sampling technique with a total questionnaire of 100 respondents. Primary data collection techniques using questionnaires. The method of data analysis using multiple linear regression previously conducted a classic assumption test consisting of normality test, heteroxidation test and multicolonierity test. The results showed that there was a positive effect on perceived security, a positive influence on information quality, a positive influence on trust and online purchase intention. Significant positive effect of perceived security on trust; significant positive effect of information quality on trust; significant positive effect of perceived security on online purchase intention; significant positive effect of trust on online purchase intention.